POTENSI MENGEMBANGKAN STARTUP UMKM HASILTANGKAPAN IKAN DENGAN STRATEGI CUSTOMER SEGMENTS - Kusumawati, Evyana Diah; Karmanis, Karmanis; Karjono, Karjono (Majalah Ilmiah Gema Maritim, 2022)
This study aims to add insight and skills of MSMEs in the field of managing caught fish with a decision support system to understand customer segment strategy, business planning and product development as well as product design for business development and product marketing through the market place. The population in this study is MSME actors who are members of a fishing group in Wonosari Kendal village. Data collection by the method of questionnaires. The methodology used uses a qualitative approach with data collection techniques using observation techniques , literature studies and interviews (interviews). The data analysis used is to use a form of qualitative descriptive method. The result of the observations obtained is that there is still a lack of understanding of the customer strategy segment of MSME actors in understanding the value of fish processed products. Having business planning and product development as a Startup player has done the work to think about how the business will work and what goals MSME players want to achieve by investing a little time and writing a business plan and still lack of product marketing through the marketplace so as to make it difficult for MSME players to market their products using the website. The conclusion that can be drawn from this study is that by increasing the insight into the skills of MSMEs in the field of managing caught fish with a decision support system understanding customer segment strategies, business planning and product development as well as product design for business development and product marketing through the marketplace can increase sales and revenue.